An Investigation into Teachers’ Views on the Supports Required to Facilitate the Inclusion of Children with Chronic Illness in Irish Mainstream Schools - McDonald, Fiona (Marino Institute of Education, 2021)
In a school setting, teachers are a major source of support for their pupils. Therefore, it is crucial teachers feel prepared with the appropriate resources to support their pupils. Advances in the medical field allow many children with chronic illnesses to integrate into mainstream primary schools and participate in classroom activities alongside their peers. Inclusive education is essential to effectively overcome diverse realities in primary school classrooms. Children living with chronic illnesses are one group of children who may need to overcome such diversities throughout their schooling journey. It is imperative that teachers are professionally prepared and supported to promote inclusive, positive educational experiences for these children. The research question that drove this research study was ‘What are teachers’ views on the supports required to facilitate the inclusion of children with chronic illness in Irish mainstream schools?’. The research design used was a qualitative method. Semi-structured interviews were conducted with 10 primary school teachers currently teaching in Ireland and each with experience in educating a chronically ill child. This research identified the deficit of education and training surrounding chronic illness evidently places an increased level of anxiety and apprehension on teachers, suggesting teachers are being placed in a position in Irish mainstream classrooms where they feel underprepared or incompetent in their role, potentially contributing to undesirable consequences for both chronically ill students and their teachers. Recommendations from the study include teacher education, the availability of accurate information and standardised documentation.
Keywords: Mainstream primary schools; Inclusive Education; Children with illness; Teachers; Teachers; Inclusion (Education); Inclusive learning; Primary education